2017
DOI: 10.20959/wjpps20179-10021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Hormone Gibberellic Acid-3 on Rat Testicular Biomarkers and Its Histology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Suriamurthy and Srikumar [42] registered too differential response to the gibberellic acid (GA3) doses offered to rats. Levels of cholesterol, triglyceride, protein, albumin, urea, uric acid and creatinine were augmented with that of malondialdehyde (MDA) and glutathione peroxidise (GPx) at all doses of GA3 used.…”
Section: Discussionmentioning
confidence: 99%
“…Suriamurthy and Srikumar [42] registered too differential response to the gibberellic acid (GA3) doses offered to rats. Levels of cholesterol, triglyceride, protein, albumin, urea, uric acid and creatinine were augmented with that of malondialdehyde (MDA) and glutathione peroxidise (GPx) at all doses of GA3 used.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with several studies that proved the histopathological alterations induced by gibberellic acid. GA resulted in damage of testicular cells, reduced testicular weight, induced a disturbance in the testicular architecture, disorganization of spermatogenic cells, widening of intercellular spaces as well as intertubular spaces, focal separation of germinal epithelium from the basement membrane, cytoplasmic vacuolation, pyknosis also exfoliation of spermatogenic cells into the tubules lumen [5,15,30] . Some studies demonstrated that GA caused morphometric alterations in testicles and disorders in spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GA caused a reduction in the size of seminiferous tubules, a significant decrease of both germinal epithelium height and the diameter of seminiferous tubules. Concerning spermatogenesis, GA induced hypospermatogenesis and a reduction in all stages of spermatogenesis, as well as a significant decrease in sperm count in the lumen of seminiferous tubules and epididymal sperm viability [1,5,30,31] Previous studies have reported that testicular toxicity induces alterations in morphometric assessments and spermatogenesis. A significant reduction in the diameter and germ cell height of seminiferous tubules was recorded in testes of rats treated with tacrolimus when compared with the control rats [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-term high dose administration of GA3 has been shown to cause increased testicular weight and decreased sperm count in male albino rats (16). Another study found markedly reduced aspartate transaminase (AST) and alanine transaminase (ALT) enzyme activities in the testes of rats exposed to GA3, which was explained by the possible toxic effect of GA3 on the testes, resulting in injury to testicular cells (17). A study with neonatal rats The change in IL-10 levels in the subchronic treatment group.…”
Section: Discussionmentioning
confidence: 99%